Determinants of product innovation performance in aviation industry in Saudi Arabia - Abdullah Alhamad; Hashed Mabkhot (Economies, 2023)
Innovative technology significantly transforms numerous activities and operations in the logistics sector across various industries, including the aviation sphere. This primary quantitative research aimed to explore the evolution of logistics and supply chain management in the digital age for aviation companies in Saudi Arabia. The research involved conducting a survey among 104 supply chain and technology personnel from Saudi Cargo and its affiliate firms in Saudi Arabia. Partial least squares (PLS-SEM) was used for data analysis to determine the relationships between three independent variables: market intelligence quality (MIQ), manufacturing-marketing coordination (MMC), and supply chain intelligence quality (SCIQ), with product innovation performance (PIP) as the dependent variable. The results indicated that SCIQ and MIQ have a positive and significant statistical relationship with PIP. Nonetheless, the findings disproved that the MMC gives insights into consumer needs directly affecting PIP. From this study, it can be concluded that aviation companies should improve their supply chain systems, marketing domain, and manufacturing marketing coordination to realize the improved performance of their product innovations in the contemporary digital era.
Keywords: 330; manufacturing-marketing coordination (MMC); market intelligence quality (MIQ); supply chain intelligence quality (SCIQ)